Summer feeding ecology of great pampa-finches, Embernagra platensis at Laguna de Guaminí, Buenos Aires, Argentina - Ferman, Laura M. (2010)
The aim of this study was to assemble data on the summer feeding ecology of the Great Pampa-finch, Embernagra platensis at the Laguna de Guaminí, Buenos Aires, Argentina, and to explore the differences related to the dietary patterns for each sex between winter and summer when possible. The stomach contents of 43 birds were analyzed. The animal fraction was composed of Hymenoptera (45.1%), Coleoptera (32.4%), Lepidoptera (6.0%), Araneae (5%) and Orthoptera (3.2%). The application of the index of relative importance (IRI) resulted in 1490.4 for Coleoptera, 428.5 for Hymenoptera and 162.5 for Lepidoptera caterpillars. The vegetal fraction consisted of Triticum aestivum (26.9%), Cyperaceous (25%), Poaceae (Gramineae) (19.3%) and Panicum sp. (11.2%). The IRI values were 893.8 for Triticum aestivum, 174.5 for Gramineae, 126.5 for Panicum sp. and 112.8 for Scirpus sp. The food niche width was 0.33 for both sexes; the diversity index resulted in 1.06 for females and 1.33 for males and specific diversity ranged from 1.87 to 2.84. A canonical component analysis (CCA) was performed on environmental and morphometric variables, and a Monte Carlo test confirmed the canonical correlations. A t-test showed that some birds harmonized with a logarithmic model and some with a geometric curve. During the summer, Embernagra platensis ingests Hymenoptera and Coleoptera more often than seeds, suggesting that two biological mechanisms could be taking place in this bird.